The Effect of Regional Winds on Subtidal Along‐Inlet Currents at Oregon Inlet, NC. Issue 8 (16th August 2022) - Humberston, J. L.; Lippmann, T. C.
Abstract: Wind influence on tidal inlet hydrodynamics is examined using 40 days of wind, water level, and current observations collected in Spring 2019 at Oregon Inlet, NC, a large (1 km wide, 1–13 m deep) meso‐tidal inlet with complex delta systems. Wind velocities through the inlet (ranging 0–18 m/s) are modulated at subtidal timescales and are well correlated ( R = 0.87) to a subtidal component of the water level slope through the inlet. The subtidal wind and water level slope are also well correlated to the subtidal current along the principal flow axis in the main inlet channel ( R = 0.92 and 0.96, respectively). In combination with findings from previous studies, these findings suggest that regional winds induce the subtidal water level slope through the inlet by causing opposing setup/setdown to either side of the inlet. A force balance at the inlet demonstrates that the wind‐induced pressure gradient forces the subtidal currents, with wave forcing and local wind shear acting as lower‐order influences. The magnitude of the subtidal current is substantial, exceeding that of the tidal currents 45% of the time. Cumulatively, these findings indicate that regional winds exert a first‐order control on the currents at Oregon Inlet and cause irregular hydrodynamic patterns not well described by the traditional inlet classification scheme. Regional geographic characteristics may contribute to the high level of wind influence at Oregon Inlet, but similar processes are likely to be important to net flow dynamics at other inlets with large, shallow inland water bodies. Plain Language Summary: Tidal inlets are constricted coastal channels maintained by the flow and are particularly common along barrier island systems where they have important implications for the flux of sediments along the coast. The traditional tidal inlet classification system is based on the relative strength of tides and waves; however, mounting evidence suggests winds may also be an important control of inlet dynamics. This works uses observations of winds, currents, and changes in water levels at Oregon Inlet, NC, to examine the role of local and regional winds in altering tidal inlet currents. Results suggest that regional winds induce a water level gradient through the inlet that varies over time periods longer than tides (>12 hr), and that this gradient then forces a current through the inlet over the same timescales. The magnitude of the wind induced current exceeds that of the tidal current 45% of the time and far exceeds contributions from waves, implying that winds may play an underappreciated role in tidal inlet dynamics. Improving our understanding of wind control on tidal inlets has important implications for dredging efforts common to tidal inlets, for numerical models simulating island chain evolution, and to the navigation of vessels that use charts to determine times of safe transit based on expected water levels and currents. Key Points: Observational data suggest regional winds induce a water level gradient through Oregon Inlet that varies over subtidal time scales Subtidal water level gradients induced by regional winds account for 92% of the variance of along‐inlet subtidal currents Subtidal currents through the inlet are of the same order as the tidally driven currents and exceed the tidal currents 45% of the time